Modeling studies of the natural state of the Krafla geothermal field, Iceland - Bodvarsson, G.S.; Pruess, K.; Stefansson, V.; Eliasson, E.T. (Lawrence Berkeley Laboratory, 1982)
The modeling of the natural state of the Krafla system has yielded results that closely match all available field data, and agree with a conceptual model developed from geochemical observations. Furthermore, studies of the sensitivity of various parameters give valuable insight into the permeabilities of different reservoir zones, thermal conductivity of the caprock, rates and enthalpies of natural recharge and discharge, and various other important reservoir parameters. The model presented here is two-dimensional, and only considers a part of the old wellfield. In the future, we hope to develop a natural-state model for the entire Krafla system, taking into account the three-dimensional nature of fluid flows.